'Ancient' Tensions and Local Circumstances: Loyalist Freemasons in Shelburne Nova Scotia. (17th December 2015) - Huskins, Bonnie
Abstract : Many American Revolutionary War Loyalists who migrated to Shelburne Nova Scotia were Ancient freemasons, who attempted to transplant fraternal rituals and traditions in their new community. Unfortunately the civilian lodges that they established proved to be short-lived. This case study of Shelburne provides historians with an opportunity to analyse why masonic lodges sometimes fail. In Shelburne, this may attributed to local factors, most significantly a socio-economic decline which hit the settlement almost immediately upon arrival. But the fractiousness of one of the lodges, Solomon's Lodge No. 5 Provincial, is also a reflection of a broader tension within Ancient freemasonry between universal brotherhood and self-interest. Only further research will corroborate whether this pattern also extended to other Loyalist lodges in Nova Scotia.